2014
DOI: 10.1186/1471-2261-14-62
|View full text |Cite
|
Sign up to set email alerts
|

The relation of location-specific epicardial adipose tissue thickness and obstructive coronary artery disease: systemic review and meta-analysis of observational studies

Abstract: BackgroundThere is growing evidence about the importance of epicardial adiposity on cardiometabolic risk. However, the relation of location-specific epicardial adipose tissue (EAT) thickness to coronary atherosclerotic burden is still unclear.MethodsThis meta-analysis was used to study the relations between location-specific EAT thickness and obstructive coronary artery disease (CAD). A systemic literature search to identify eligible studies that met the inclusion criteria from the beginning until January 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 46 publications
3
35
0
4
Order By: Relevance
“…Furthermore some investigators found that epicardial fat thickness measured at the left atrioventricular groove was the best predictor of obstructive coronary artery disease (116,338). This finding was confirmed in a meta-analysis but confirmation is needed in other populations than Asians (337).…”
Section: What Should Be Measured and How?mentioning
confidence: 89%
“…Furthermore some investigators found that epicardial fat thickness measured at the left atrioventricular groove was the best predictor of obstructive coronary artery disease (116,338). This finding was confirmed in a meta-analysis but confirmation is needed in other populations than Asians (337).…”
Section: What Should Be Measured and How?mentioning
confidence: 89%
“…Second, we could not evaluate the impact of location-specific EAT on the development of plaques in adjacent coronary arteries. Current evidence suggests an association between the location-specific EAT thickness at the atrioventricular groove and the presence of obstructive CAD 41) , so evaluation of this relationship would provide interesting insight regarding the pathobiology of EAT on the development of coronary atherosclerosis. Third, we excluded participants with metabolic syndrome from this study, since there is a strong relationship between the presence of metabolic syndrome and EAT.…”
Section: Discussionmentioning
confidence: 99%
“…20- 22 Wang et al showed that EAT thickness in the LAVG, but not EATV, was significantly associated with coronary atherosclerosis; 20 also, a meta-analysis confirmed that increases in location-specific EAT thicknesses at the LAVG are associated with obstructive CAD. 21 Our previous study found that EATLAD was greater in the CAD group than in the non-CAD group, and that it had added diagnostic value over other conventional risk factors. 22 Ohyama et al reported that the local EATV around the LAD, but not around the RCA or LCX, was significantly increased in patients with LAD spasms, suggesting the involvement of coronary EAT in the pathogenesis of coronary spasms, a form of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%